PEMETAAN PERSEPSI MERK LAPTOP DI KALANGAN MAHASISWA MENGGUNAKAN ANALISIS KORESPONDENSI BERGANDA (Studi kasus: Mahasiswa Universitas Diponegoro Semarang) - Anissa Pangastuti; Moch. Abdul Mukid; Sudarno Sudarno (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2013)
The growth of technology makes producer compete creating sophisticated, modern, and practical tools. One of them is competing creating notebook. Some brands that more develop than other brands in the market are Toshiba, Acer, Asus, HP and Dell. This research studies about positioning one brand against other brands in the market and proximity between all brands that affected by some factors. There are, processors, designation notebook for consumer, features, endorsement and guarantee, endurance notebook against damage, and the distant age of notebook consumption when it has damage in hardware for the first time. Because there are so many factors that affecting perceptual mapping and positioning notebook at the market, hence it need to be analyzed using multiple correspondence analysis. Multiple correspondence analysis is an expansion technique from simple correspondence analysis which is a multivariate technique graphically used for exploration data from a multi-way contingency table. The result of this research makes conclusion that there is a similarity between Acer and HP notebook. This statement be marked with proximity of point Acer and HP. It can be seen from the incision magnitude between both of that brands. There are both of them be used for graphic and designing, have the same complete features and for time of damage for the first time that both of that brands experienced are at age > 3 years